[PP.11.28] UNRAVELING THE URIC ACID IN THE CLUSTER OF CARDIOMETABOLIC RISK FACTORS EARLY IN LIFE: A PROSPECTIVE STUDY. (September 2017) - Redon, P.; Torro, I.; Alvarez, J.; Redon, J.; Lurbe, E.
Abstract : Objective: The present prospective research, starting at birth, was undertaken to analyze factors related to the uric acid in children at 5 years old. Design and method: One hundred and fifty four Caucasians of both sexes (77 females), of European origin, born at term were included. After the initial evaluation on the second day of life, infants were followed up and growth pattern prospectively recorded. At five years, office BP measurements were performed and fasting blood sample was obtained to measure glucose, insulin, lipid profile, and uric acid. All subjects were normotensives, no diabetes neither dyslipidemia were present. Results: In this prospective study, uric acid at five years depends positively on the increment of weight from birth (p < 0.001) and inversely of the birth weight (p < 0.05). Furthermore, uric acid was significantly correlated with current weight (r = 0.25; p = 0.003), current height (r = 0.17; p = 0.04), office SBP (r = 0.23; p = 0005), insulin (r = 0.36; p = 0.001), and HDL (r = −0.30; p = 0.001). In a multiple regression analysis insulin, and HDL cholesterol were independent determinants of uric acid when, sex, current weight, birth weight, SBP, and Log triglycerides were also included (r2 = 0.23). The weighted impact of uric acid on metabolic parameters and office SBP, adjusted by sex and body weight, are shown in the Table.https://services.aimgroup.it/ASPClient/files/3465/Abstract/669_20170102111446.jpg Figure. No caption available. Conclusions: Uric acid is associated with metabolic parameters independent of office BP. Metabolic status at 5-year-old in children born at term may be influenced by perinatal events and postnatal rapid weight gain with clinical implications that require active intervention to prevent or reverse upward crossing of weight percentiles.